2023
DOI: 10.3390/ijms24119385
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Genes as a Key to Identification of Inverse Comorbidity of Huntington’s Disease and Cancer

Abstract: Cancer and neurodegenerative disorders present overwhelming challenges for healthcare worldwide. Epidemiological studies showed a decrease in cancer rates in patients with neurodegenerative disorders, including the Huntington disease (HD). Apoptosis is one of the most important processes for both cancer and neurodegeneration. We suggest that genes closely connected with apoptosis and associated with HD may affect carcinogenesis. We applied reconstruction and analysis of gene networks associated with HD and apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…This was followed up by Ehrnhoefer et al who suggested that upregulation of p53 found in mHTT containing neuronal and peripheral cells lowers the apoptotic threshold [ 40 ]. In a new publication, the authors analyzed gene networks associated with HD, apoptosis, and cancer and identified genes pointing on apoptosis along with lipid metabolism dysregulation and cell homeostasis as key processes [ 41 ]. In cell and mouse models Murmann et al investigated the effects of trinucleotide repeat (TNR) siRNA in cancer cell and found the siCAG repeat to be the most toxic suggesting that RNA interference could be involved in neurodegeneration as well as cancer suppression mechanisms [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was followed up by Ehrnhoefer et al who suggested that upregulation of p53 found in mHTT containing neuronal and peripheral cells lowers the apoptotic threshold [ 40 ]. In a new publication, the authors analyzed gene networks associated with HD, apoptosis, and cancer and identified genes pointing on apoptosis along with lipid metabolism dysregulation and cell homeostasis as key processes [ 41 ]. In cell and mouse models Murmann et al investigated the effects of trinucleotide repeat (TNR) siRNA in cancer cell and found the siCAG repeat to be the most toxic suggesting that RNA interference could be involved in neurodegeneration as well as cancer suppression mechanisms [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is rarely reported on the death certificates of individuals with HD (Sørensen et al, 1999;Bragina et al, 2023). In those with HD, the length of the mHtt repeat sequence is negatively correlated with cancer incidence (Murmann et al, 2018a,b).…”
Section: Cancermentioning
confidence: 99%